Criminal Sanctions and State Loss: A Review of Corruption Sentencing Under the New National Penal Code - Jessyca H. Picauly; Adolof Seleky; Imanuel J. Lawalatta (CV. Era Digital Nusantara, 2026)
This research examines the transformation of corruption sentencing under Indonesia’s Law Number 1 of 2023 (National Penal Code) compared to Law Number 31 of 1999. Utilizing a normative-juridical approach, the study analyzes Article 603 of the new code, which significantly reduces the minimum imprisonment from four to two years. Critics argue this undermines the